Gastric function in diabetic gastroparesis assessed by ultrasound and scintigraphy. Issue 4 (11th August 2021) - Steinsvik, Elisabeth K.; Sangnes, Dag A.; Søfteland, Eirik; Biermann, Martin; Assmus, Jörg; Dimcevski, Georg; Gilja, Odd Helge; Hausken, Trygve
Abstract: Background: Gastroparesis is a severe diabetes complication characterized by delayed gastric emptying. We examined patients with symptoms of diabetic gastroparesis using gastric emptying scintigraphy and ultrasound drink test. The primary aim was to investigate how ultrasound could provide information about gastric motility features in diabetic gastroparesis. Material and methods: We prospectively included 58 patients with diabetes (48 type 1) with symptoms of gastroparesis and 30 healthy controls. Patients were examined with ultrasound of the stomach in a seated position after drinking 500 ml low‐caloric meat soup, at the same time recording dyspeptic symptoms. The following day, they were examined with gastric emptying scintigraphy, defining gastroparesis as >10% retention after 4 h. Key Results: We found motility disturbances in the proximal stomach measured by ultrasound in patients with diabetic gastroparesis. A linear mixed effects model including repeated ultrasound measurements revealed a slower decrease of the proximal stomach size in gastroparesis compared to healthy controls ( p  < 0.01), and the proximal diameter at 20 min was correlated to scintigraphy at 4 h ( r  = 0.510, p  = 0.001). The antrum in patients with diabetic gastroparesis was twice as large compared to healthy controls ( p  = 0.009), and fasting antral size was correlated to gastric emptying scintigraphy ( r  = 0.329, p  = 0.013). Both diabetes patients with and without gastroparesis had impaired accommodation ( p  = 0.011). Conclusions and Inferences: On ultrasound, we found delayed reduction of proximal stomach size and impaired accommodation after a liquid meal in patients with gastroparesis, emphasizing the role of the proximal stomach. Furthermore, we found antral distention in gastroparesis patients. Abstract : In a prospective study of 58 patients with suspected diabetic gastroparesis, gastric ultrasound demonstrated impaired gastric accommodation and delayed gastric emptying of the proximal and distal stomach.